PENGARUH KUALITAS PELAYANAN PEMAHAMAN PERATURAN PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DAERAH DI KABUPATEN TOJO UNA-UNA - Kadir, Abdul (Katalogis, 2017)
The study aims to determine and analyze the influence of service quality, understanding of tax regulations, and tax penalties on the compliance of local taxpayers in Tojo Una-Una. Population consists of 646 taxpayers, and sample is 100 people. Data processed with programÂ statistical product and service solution (SPSSÂ 18.0) with multiple linear regressions analysis. The results show that: 1) service quality, understanding of tax regulations, and tax penalties significantly influence the compliance of local taxpayers in Tojo Una-Una; 2) service quality insignificantly influences the compliance of local taxpayers in Tojo Una-Una; 3) understanding of tax regulations significantly influences the compliance of local taxpayers in Tojo Una-Una; 4) tax penalties significantly influence the compliance of local taxpayers in Tojo Una-Una.